Architecting Resilient Network Operations: A Comprehensive Framework for Large-Scale Enterprise SD-WAN and Zero Trust Implementation - Imran Abdul Majeed Qadri (International Journal of Computational and Experimental Science and Engineering, 2025)
I developed and implemented a revolutionary framework that transforms traditional enterprise network operations through my strategic integration of software-defined wide area networking and zero trust security principles. My architectural blueprint uniquely combines Cisco Viptela SD-WAN and ACI fabric technologies with my proprietary zero trust routing methodology to achieve unprecedented automation and security across extensive multi-site deployments. I engineered a novel multi-protocol optimization system that harmonizes BGP, EIGRP, and OSPF routing mechanisms, delivering superior resilience and sub-second failover capabilities in hybrid network environments. My zero trust routing enforcement provides advanced segmentation for SCADA traffic isolation while implementing my policy-based prioritization system for critical infrastructure control packets. Through my comprehensive framework, I addressed complex cloud-edge integration challenges and optimized ISP peering management across major cloud providers. My implementation demonstrates quantifiable improvements including 0.7-second average failover times, 4.2M in annual operational savings, and 100% security compliance across large-scale enterprise deployments, establishing a new standard for modernized network infrastructure.